Efforts to Improve Discipline of Sidoarjo Regency Environmental and Hygiene Service Employees - Pamungkas, Tri Yan Putra; Mursyidah, Lailul (Universitas Muhammadiyah Sidoarjo, 2020)
Work discipline is highly emphasized to civil servants for the success of an organization or government agency, which is more broadly a common goal that has been designed together. The purpose of this study is to analyze and describe the level of performance and factors that affect the performance of employees at the Department of Environment and Hygiene, Sidoarjo Regency. The method used is a qualitative method with a descriptive approach. This study focuses on one performance indicator, namely discipline. Data collection techniques in the form of observation, documentation, and interviews with sampling technique. The data analysis technique is by collecting data, presenting data, reducing data, and drawing conclusions. The results of this study indicate that employees at the Environmental and Hygiene Service of Sidoarjo Regency still have employees who are late and neglect finger print attendance. In addition, there is a lack of motivation from leaders to their subordinates not to be late.